Role of decision style and knowledge in awareness influence to phishing detection in higher education - Muh. Bafadhal Kurnia Alamsyah; Candiwan Candiwan (Bulletin of Electrical Engineering and Informatics, 2026)
Phishing attacks are a significant cybersecurity threat in higher education, where employees handle sensitive data such as student records, financial transactions, and research information. This study investigates the relationship between information security awareness (ISA), intuitive decision style (IDS), and phishing detection confidence (PDC), while assessing the moderating role of phishing email knowledge (PEK). A quantitative approach was employed, using a structured questionnaire distributed to 120 employees at XYZ University in Indonesia. Data were analyzed using moderated mediation analysis with PROCESS Macro. The findings indicate that ISA positively influences IDS, but an overreliance on intuition negatively impacts PDC. PEK significantly moderates this relationship, reducing the negative effects of intuitive decision-making. The results emphasize the importance of cybersecurity awareness and phishing-specific training programs to enhance detection confidence. Organizations should integrate security awareness programs with phishing simulations and automated detection tools to strengthen their cybersecurity defenses. This study is limited by its focus on a single organization and reliance on self-reported measures. Future research should explore additional cognitive and contextual factors influencing phishing susceptibility to develop more comprehensive security strategies.